The effect of macular pigments on vision - Bonczar, Anna; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The eye responsible for visual processes is exposed to the side effects of radiation. The presence of oxygen and photon is sufficient for the formation of free radicals, which induce irreversible and incurable degenerative changes within the macula, retina and lens. There is an increasing body of evidence to support protective role of macular pigments – carotenoids: lutein and zeaxanthin – in preventing retinal and lens damage. As a result, lutein and zeaxanthin dietary supplements have become increasingly more popular in recent years and an increasing number of reports indicate that their intake improves visual acuity and quality of vision, whilst contributing to the prevention of age-related macular degeneration. Vision improvement seen in patients using lutein and zeaxanthin supplements can be attributable to changes in the underlying biological and/or optical processes. The paper discusses the impact of carotenoids on vision.